Integrated management strategies against tomato collar rot (Sclerotium rolfsii): A characterisation to management study - A, ANBU; K, SANJEEVKUMAR; P, BALABASKAR; T, DEEPIKA (The Indian Journal of Agricultural Sciences, 2026)
The study was carried out during winter (rabi) season of 2022–2023 at Dharmapuri and Cuddalore districts of Tamil Nadu to formulate an integrated strategy for managing tomato collar rot, a major disease caused by Sclerotium rolfsii Sacc. The survey identified Keerapatti village as a hotspot with 47.53% incidence. Among fifteen isolates, Sr10 was the most virulent, causing 62.30% disease incidence in pot experiments. Molecular characterisation confirmed the pathogen as S. rolfsii and antagonists as B. subtilis showing 98.8–99.0% nucleotide identity with reference sequences. A native antagonist, B. subtilis isolate Bs3, exhibited strong antifungal activity with 78.94% inhibition in vitro, significantly suppressing mycelial growth (77.41%) and sclerotial formation (84.40%) through secondary metabolites. Molecular docking analysis further demonstrated that key antifungal compounds from B. subtilis showed strong binding affinity with pathogen target proteins, suggesting disruption of pathogenicity-related mechanisms. In pot trial, the integrated treatment (T7), combining B. subtilis with neem cake, was most effective, reducing collar rot incidence by 78.29%. Additionally, treated plants exhibited enhanced vigour, with maximum plant height, germination rate, and fruit yield. Collectively, these findings highlighted that integrating B. subtilis and neem cake, supported by docking-based mechanistic evidence, offers a sustainable and eco-friendly alternative to chemical fungicides for collar rot management in tomato (Solanum lycopersicum L.).